DESIGN INFORMATION SYSTEMS OF PRODUCTION RESULTS IN THE RAJAWALI BROMO CONVECTION INDUSTRY, MAKASSAR - Lantara, Dirgahayu; Pawennari, Andi; Padhil, Ahmad; Malik, Rahmaniah; afiah, Irma nur; Cahya, Astin (Journal of Industrial Engineering Management, 2021)
The development of the era where everything is instantaneous and fast as it is today must be supported by the development of increasingly sophisticated information technology. One of the functions of this technological development is to obtain accurate and fast information. But in fact, there are still companies / organizations that have not used computer technology as a work aid, such as the Bromo Rajawali Convection which still uses the manual method of writing employee data, namely data storage still using books. Therefore, the design of an employee data management information system is carried out that can help companies control the production data of each tailor employee. The method used in this research is the Waterfall method. It is called a waterfall because the steps that are passed must wait for the completion of the previous stage and run sequentially, for example the design stage must wait for the completion of the previous stage, namely the requirements stage [1]. The Waterfall method consists of 5 stages, namely Analysis, Design, Coding, Testing and Maintenance. The purpose of this study is to design an information system that can make it easier for companies to write down employee production data accurately. From the design results, there are two factors that support the running of the system, namely administration and production data, the input form available on the system that has been designed, namely the login input form and the employee data input form, while the output form contains complete data related to employee personal data and employee production data. With the creation of a management information system in writing data on employee production, the Rajawali Bromo Convection can accelerate the search for more accurate data in the future, and applications made later by the company can be used properly as one of the employee production data systems